The Dimensions Of Emotional Intelligence And Its Relationship To Academic Achievement Of Social Studies For Students In South Batinah Governorate In The Sultanate Of Oman - Al - Harasi, Saif bin Darwish bin Said; Ibrahim, Michael (Journal of Educational and Psychological Sciences, 2019)
The current study aimed at revealing the relationship of the dimensions of emotional intelligence according to the theory of Golman on the achievement of the study of the subject of social studies for students of South Batinah province in the Sultanate of Oman. The researchers used the descriptive correlation approach. The tool consisted of a questionnaire consisting of (50) Questions. Has been applied to all the states of South Batinah province consisting of six states, using the simple random method of (380) students. Using statistical methods in the SPSS program, the results of the study showed a statistically significant relationship at the level of (0.001 = α) for all dimensions of emotional intelligence towards the scholastic achievement of the subject of social studies, with the correlation between them (0.26). Emotional intelligence was associated with empathy after 0.89, emotional management of 0.89, social skills of 0.87, self-awareness of 0.83, and self-motivation of 0.81. The results showed that there were no statistically significant differences at (α = 0.05) between scholastic achievement according to gender variable. The statistical function was 0.000 for the seventh grade with an average of (4.2), while the average grade was (3.7).